A Conceptual Framework for the New Zealand Tort of Intrusion - Moreham, Nicole A (Victoria University of Wellington Law Review, 2016)
This article examines the desirable scope of the New Zealand tort of intrusion into seclusion. It begins by developing a six-part taxonomy of common law privacy interests and then, using that taxonomy as its starting point, asks which privacy interests the New Zealand intrusion tort should cover. It argues that although the intrusion tort is a very welcome addition to New Zealand common law, it is important that its parameters are clearly delineated. The best way to achieve that, it is suggested, is by recognising that unwarranted listening, watching or recording of private activities is the gravamen of the new tort.